Hubungan Konsep Diri Dengan Tingkat Stress Dalam Menyusun Skripsi Pada Mahasiswa Ekstensi Kelas IIIB Di Universitas Indonesia Maju Tahun 2022 : Relationship of Self-Concept with Stress Level in Completing Thesis in Class IIIB Extension Students at the University of Indonesia Maju in 2022 - Maulana, Asep (Dohara POAJ, 2023)
Introduction: Based on the data from PDDikti Director General of Education, it is known that the number of students currently reaches 9,188,703 students from 38,896 study programs in various majors and comes from 4,552 tertiary institutions throughout Indonesia. A thesis can be an obstacle in completing studies if students in their lives do not have high enthusiasm and play an active role in solving problems that exist when working on the thesis. The stress experienced by students will result in changes in their bodies and mind. Stress that feels heavy can trigger a person to behave positively from stress in the form of increasing creativity and triggering self-development, as long as the stress experienced is within the limits of individual capacity. While the negatives such as smoking, alcohol consumption, brawls, free sex, and even drug abuse. The purpose of this study was to determine the relationship between self-concept and stress levels in preparing a thesis for third-grade extension students. Methods: This research is a quantitative study with a correlational design, which is a study to determine the relationship between two variables. This study uses a cross-sectional approach. The population in this study were 46 students of the Extension IIIB Nursing Science class at the University of Indonesia Maju in 2022. The sampling technique used was the total population technique. The sample in this study was 46 respondents. The research instrument used was a questionnaire. The statistical test used is chi-square. Results: The relationship between self-concept and stress levels in compiling a thesis for class IIIB extension students at the University of Indonesia Maju in 2022 obtained a p-value = 0,007; meaning the p-value < α (0,05). Discussion: there is a relationship between self-concept and the level of stress in compiling a thesis on extension students of class IIIB.